Convergence in military expenditure and economic growth in Africa and its regional economic communities: Evidence from a club clustering algorithm - Charles Shaaba Saba; Nicholas Ngepah (Cogent Economics & Finance, 2020)
This study examines the convergence in military expenditure and economic growth for a panel of 35 African countries between 1990 and 2015. We employ the Phillips and Sul methodology to achieve our objective. Overall, the results at Africa level reveal no evidence of convergence in military expenditure and growth. However, after robustness tests, the final club classification results do support the hypothesis of club convergence for the two variables. The results of the analysis show that there exist: (i) two convergence clubs for military expenditure; and (ii) five convergence clubs for growth. The empirical findings further suggest that the Regional Economic Communities (RECs) form distinct convergent and divergent clubs, exhibiting considerable heterogeneity in the underlying defence and growth patterns. In addition, the empirics confirm that the countries in each region appear to have chosen dissimilar defence and growth transition paths. The policy implications are discussed in the concluding section of this study.
Keywords: H560; O47; O55; 330; Africa; Convergence Club; Economic Growth; Log t regression test; Military Expenditure